Optimal Timing for Early Excision in a Deep Partial Thickness Porcine Burn Model. Issue 1 (January 2017) - Toussaint, Jimmy; Chung, Won Taek; Mc Clain, Steve; Raut, Vivek; Singer, Adam J.
Abstract : Many deep partial thickness burns require more than 3 weeks to heal resulting in disfiguring and dysfunctional scarring. Early excision of the eschar has been shown to improve outcomes in deep burns; however, the optimal timing of the excision remains controversial. We compared wound healing and scarring of deep partial thickness burns that were excised at different time points in a porcine model. Deep partial thickness burns (2.5 by 2.5 cm each) were created on the backs of six anesthetized pigs using a previously validated model. The burns were randomly assigned to excision at days 2, 4, or 7 using an electric dermatome. Full thickness 4-mm punch biopsies were obtained at several time points for determination of re-epithelialization and at day 28 for determination of scar depth. Digital imaging was used to calculate percentage wound contraction at day 28. There were no statistically significant differences in wound re-epithelialization at any of the studied time points. Scar depth and percentage wound contraction were also similar among the wounds excised at 2, 4, and 7 days (4.4 ± 1.1 mm vs 3.9 ± 1.1 mm vs 4.1 ± 1.2 mm and 52.9 ± 17.9% vs 52.6 ± 15.6% vs 52.5 ± 13.8%, respectively). Timing of eschar excision (at 2, 4, or 7 days) does not affect the rates of re-epithelialization and scarring in a deep partial thickness porcine burn model. Timing of eschar excision may not change outcomes if performed within the first 2 to 7 days after injury.